2015
DOI: 10.1111/jace.13582
|View full text |Cite
|
Sign up to set email alerts
|

Direct Imaging of the Distribution of Nd3+ Ions in Glasses Containing PbS Quantum Dots

Abstract: The influence of Nd3+ ions was investigated on the precipitation and optical properties of PbS quantum dots (QDs) inside silicate glasses. The diameters of the PbS QDs decreased as the concentration of Nd3+ in the glass increased as evidenced by blue shifts in the absorption and photoluminescence spectra. Electron energy loss spectroscopy shows that Nd3+ ions exist preferentially inside the PbS nanocrystals rather than in the glass matrix. We postulate that Nd–O clusters are preserved during heat treatment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…5d) and it is consistent with the results of electron energy loss spectroscopy (EELS) (Fig. S1) 28 . The elemental concentration profile along one QD showed that [Pb] increased to ~10 at.%, and [Nd] increased to 12 at.% (Fig.…”
Section: Resultssupporting
confidence: 89%
“…5d) and it is consistent with the results of electron energy loss spectroscopy (EELS) (Fig. S1) 28 . The elemental concentration profile along one QD showed that [Pb] increased to ~10 at.%, and [Nd] increased to 12 at.% (Fig.…”
Section: Resultssupporting
confidence: 89%
“…Shim and co‐authors also found that the lifetime of Er 3+ : 4 I 13/2 energy level does not change with the heat‐treated process . In the Nd 3+ ‐doped QDs glass, the lifetime of the Nd 3+ : 4 F 3/2 energy level hardly changed with the generation of QDs . The Nd 3+ ions are bonded with the oxygen atoms and their local environments are unaffected by heat treatment.…”
Section: Resultsmentioning
confidence: 97%
“…doped Tm 2 O 3 , La 2 O 3 , and Ho 2 O 3 to control the precipitation of PbS QDs in glasses, and observed a similar blue shift in the peak wavelengths of the absorption and PL bands with increasing RE concentration . Recently, electron energy loss spectroscopy (EELS) analysis has revealed that the concentration of RE ions, such as Nd 3+ , is considerably higher inside the PbS nanocrystals than in the glass matrix . However, the role of RE ions in the precipitation of QDs is not yet clearly understood.…”
Section: Introductionmentioning
confidence: 87%